Program Pengembangan Keberagamaan Peserta Didik dan Pendidik Di SDIT Insan Teladan - Deasy Nurma Hidayat (Institut Studi Islam Muhammadiyah (ISIMU) Pacitan, 2022)
This study discusses the religious development program. The religious development program is implemented for students and educators. The purpose of this study is to find out how the religious development program for students and educators. The location of this study was conducted at a school in the area of ​​Cileunyi, Bandung Regency, namely SDIT Insan Teladan. This research method uses participatory descriptive analytical methods. The participants of this study were the interviewees, namely the principal. The conclusion is, there are two special religious programs for students developed at this school. There are also several religious development programs that are planted for educators in this school. Both religious development programs for students in this school have been running and developing well, but there are several aspects that need to be developed again, so that all aspects in both programs can run optimally. Likewise, the religious program developed for educators in this school has also generally been running quite well, but there are aspects that need to be developed again.